Effectivenesse Booklet Media Education On Improving Worker Hygiene And Sanitation Practices Household Cracker Industry In Silaberanti Sub District Palembang - Rina, Zairinayati; Ciptawan Wijaya, Denny; Surya Ananda, Dinda (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2025)
The existence of a food home industry is a source of business that can support people's lives so it is necessary to guarantee the safety aspects of the food products produced. The emergence of foodborne diseases is a public health problem that often occurs in the modern era. Through the provision of education with visual media e-booklets are expected to be able to increase the knowledge of working owners and employees. The purpose of this study was to find out the differences in the behavior and hygiene practices of domestic industry workers. This research method is quasi-experimental and uses a time series experiment. The components measured by sanitation facilities, knowledge and behavior of washing hands include aspects of processing facilities, water supply, food storage, cooking equipment and food containers, how to store food and prepared food, food serving, and food distribution. Frequency distribution data analysis and Paired sample T test in pairs. The results showed that the gender of the respondents was 70% female, the age of the respondents was 70% less than 44 years, the results of the different test obtained the P-value for the variable sanitation facilities before and after counseling was 0.009 and for hand washing obtained a P-value of 0.000. The conclusion is that there are differences in sanitation facilities, knowledge and practice of washing hands when working before and after counseling with e-booklets.